Women and Minority Faculty in the Academic Workplace Recruitment, Retention, and Academic Culture - Aguirre, Adalberto, Jr.; ERIC Clearinghouse on Higher Education; George Washington Univ., Washington, DC. Graduate School of Education and Human Development (Washington, DC : ERIC Clearinghouse on Higher Education, 2000)
Institutions of higher education have attempted to diversify their faculty by recruiting women and minorities. However, recruitment has taken place without an understanding of the social forces that shape the professional socialization and workplace satisfaction of women and minority faculty. Conclusions drawn by the author about the plight of women and minority faculty in the academic workplace include: (1) The number of women and minority faculty in higher education has been increasing though they remain underrepresented in higher education relative to their numbers in the U.S. population; (2) The academic workplace has been described as chilly and alienating for women and minority faculty because they are ascribed a peripheral role in the academic workplace and are expected to perform roles that are in conflict with expectations; (3) Women and minority faculty are less satisfied than White male faculty with the workplace because they perceive themselves to be victims of salary inequities and a biased reward system; and (4) Women and minority faculty are also perceived as less competent than White male faculty. As a result, White male faculty often discredit feminist and minority research. (Contains 15 references.) (PW)
Availability: ERIC Clearinghouse on Higher Education, One Dupont Circle, Suite 630, Washington, DC 20036-1183. Tel: 800-956-7739 (Toll Free).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: ED-99-00-0036.
ERIC Note: For the full report, see HE 033 595. Prepared in cooperation with Jossey-Bass Publishers.
Practitioners.
Teachers.
Keywords: College Faculty; Diversity (Faculty); Higher Education; Minority Group Teachers; Racial Discrimination; Sex Discrimination; Women Faculty; ERIC Digests; ERIC Publications; ERIC Digests in Full Text